Lung cyst and multinodular thyroid goiter: Keys to DICER1 syndrome diagnosis in a 16‐year‐old female. Issue 12 (17th July 2020) - Tutor, James D.; Miller, Stephen F.; Al Zubeidi, Hiba; Sheyn, Anthony; Zhang, Jie; Williams, Regan; McGee, Rose B.
Abstract: Pulmonary cysts and neoplasms, especially congenital or occurring at a young age, should be thoroughly investigated. Evaluation for DICER1 mutations should be performed if there is a family history of this syndrome, the lung cyst/neoplasm is a pleuropulmonary blastoma, or other clinical manifestations of this syndrome are present or develop. Abstract : Pulmonary cysts and neoplasms, especially congenital or occurring at a young age, should be thoroughly investigated. Evaluation for DICER1 mutations should be performed if there is a family history of this syndrome, the lung cyst/neoplasm is a pleuropulmonary blastoma, or other clinical manifestations of this syndrome are present or develop.